ANALISIS PENGARUH FAKTOR EKONOMI DAN RELIGIUSITAS TERHADAP PERSEPSI SUPERVISOR DAN MANAJER MENGENAI INDEPENDENSI DEWAN PENGAWAS SYARIâAH (Studi Kasus pada Bank Syariâah di Indonesia) - Prasetyoningrum, Ari Kristin (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2012)
The objectives of this study are to tests the effects of economics factor (financial association and relationship of business and âfeeâ dimention) and Religious factor (charitable dimention) to Shariâa Supervisory Board (SSB) independency to prove empirically research done by Karim (1990). The primary data of this received from perception of shariâa banking managers and supervisors in Indonesia. The data were collected by using questionnaires sent to managers and supervisors. Questionnaires were distributed to 385 shariâa banking managers and supervisors and the response rate is 10, 65%. The data were analyzed by using multiple regression metode. The result of this research indicated that religious factor has positive and significant relationship with SBB independency. It also indicate that financial association and relationship of business has negative relationship and âfeeâ has positive relationship with SBB but both of them are not significant. This research finding in line with research of Karim (1990).